Pain-Related and Negative Semantic Priming Enhances Perceived Pain Intensity - Maria Richter; Christoph Schroeter; Theresa Puensch; Thomas Straube; Holger Hecht; Alexander Ritter; Wolfgang HR Miltner; Thomas Weiss (Pain Research and Management)
BACKGROUND: Negative affective and pain-related cues, such as pictures or words, have been shown to act as primes and enhance the perceived intensity of subsequent painful events. For pain-related semantic primes, it remains unclear whether this effect depends on negative valence itself or, specifically, on the pain-relatedness of the words.